Generation of a human induced pluripotent stem cell line (FDCHi010-A) from a patient with Xia-Gibbs syndrome carrying AHDC1 mutation (c.2062C > T) - Tingting Yin; Bingbing Wu; Ting Peng; Yunfei Liao; Shuangyun Jiao; Huijun Wang (Stem Cell Research, 2023)
A human induced pluripotent stem cell line (iPSC), FDCHi010-A, was derived from the peripheral blood of a 3-year-old patient with the c.2062C > T (p.R688*) mutation in the AHDC1 gene. The established cell line displayed a typical human embryonic stem cell-like morphology, exhibited a normal euploid karyotype, and fully expressed pluripotency markers. In addition, it retained the ability to differentiate to three germ layers. This cell line with a specific mutation may provide a useful tool for studying the pathogenesis and drug therapy screening of Xia-Gibbs syndrome caused by the AHDC1 gene.